Pentagon Fraud Model and Financial Statement Fraud: The Moderating Role of the Audit Committee - Rahmadania, Rosanti; Susilawati, Susi; Suryaningsih, Maria; Yuli, Rama (International Journal of Business, Law, and Education, 2026)
This research aims to analyse and provide empirical evidence on the influence of pentagon fraud indicators and their effect on financial statement fraud, moderated by audit committees, based on phenomena in state-owned enterprises (SOEs) in Indonesia. Research samples were taken from the annual reports of SOEs listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling method used in this study is purposive sampling. This research analysis uses Panel Data Regression. The research results show that pressure, opportunity, and arrogance positively influence financial statement fraud, suggesting that companies continue to engage in such fraud. The audit committee, as a moderating variable, cannot